Wildlife of Florida Factsheet: Introduction - Raoul K. Boughton (EDIS, 2018)
The Wildlife of Florida Factsheet series was created to provide the public with a quick accurate introduction to Florida’s wildlife, including both native and invasive. We hope these factsheets inspire people to investigate wildlife in their own backyard and communities and understand the amazing biodiversity of wildlife in the state of Florida.